2021
DOI: 10.1109/tasc.2021.3065879
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Damage Protection Method by Reducing Induced Current in NI REBCO Pancake Coils During Quench Propagation

Abstract: The no-insulation (NI) winding technique has been attracting attention, because NI Rare-Earth Barium Copper Oxide (REBCO) pancake coils have high thermal stability. It is an indispensable technology to generate an ultra-high magnetic field. In 2017, using the NI winding technique a world-record high magnetic field, 45.5 T, was generated by 12 insert single pancake coils with an outsert magnet, and it showed a high potential to generate 14.4 T inside a background field of 31.1 T. After the experiment, the REBCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For instance, Little Big Coil 3 (LBC3) showed that an HTS magnet could generate 14.4 T under a high field environment of 31.1 T with 1420 Amm −2 of operating current density [10]. On the other hand, in order to use HTS magnets for accelerator applications, the issues on the screeningcurrent-induced-stress [11][12][13][14][15] and overstrain occurred during quench [16][17][18][19] need to be investigated further. Hence, the HTS magnet is not an effective option in low magnetic fields and there also remain issues, but it can be considered as an essential choice in the high-field region.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Little Big Coil 3 (LBC3) showed that an HTS magnet could generate 14.4 T under a high field environment of 31.1 T with 1420 Amm −2 of operating current density [10]. On the other hand, in order to use HTS magnets for accelerator applications, the issues on the screeningcurrent-induced-stress [11][12][13][14][15] and overstrain occurred during quench [16][17][18][19] need to be investigated further. Hence, the HTS magnet is not an effective option in low magnetic fields and there also remain issues, but it can be considered as an essential choice in the high-field region.…”
Section: Introductionmentioning
confidence: 99%
“…In our magnet, the MS consists of REBCO NI turns implemented in the middle of the stainless steel (SS) OB. An and Mato [21,22] have numerically shown in 2020 and 2021 the beneficial effect of such technology in the peak temperature and stresses during quenches of an NI magnet. We can confirm it with our magnet built in 2018, which handled a sudden discharge of the outsert (and of itself) at very high field (above 28 T), and a quench at 32.5 T, without mechanical breaking of the winding.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon would happen in REBCO windings. Although several methods for the mechanical stability improvements were proposed [9], [10], it is necessary to clarify the mechanical phenomenon of both REBCO tapes and windings towards further developments of ultra-high magnetic field magnets.…”
Section: Introductionmentioning
confidence: 99%